Postsecularism as the Subversion of the Dichotomy between Science and Religion: A Theoretical Study - Gyawali, Ramesh (Bagiswori Journal, 2026)
Postsecularism’s advocacy for addressing and correcting the issues such as injustice, inequality and rendered liberty prevailed in the society amid the pervasiveness of capitalism, which puts it on a safe level; however, it is sometimes portrayed as a regressive concept as it advocates for the return of religion in the public sphere. The shortcomings of secularization project, a firm pillar of the Western Modernity, in the Western society, which was exacerbated by the unprecedented migration to the West as a consequence of globalization and religious organizations’ claim for their role in the public sphere amid the conflicts in the name of religion throughout the world marked the gradual rising of postsecularism to transform both the orthodox religion and extreme secularism in a point of reconciliation. This study endeavours to critically analyze the ideas of postsecularism, tracing its origin and mapping its evolution in the West and the East. While exploring it, the incomplete promises of secularism and modernity and the stimuli of postsecularism are accounted. Moreover, this article argues that postsecularism is a significant theoretical approach for literature and society to explore the impact of science and religion in their rigid form of dichotomy and find a way to reconcile them, emphasizing the just and equal human and social relations. The findings reveal that postsecularism unearths and tries to correct the injustice and inequality prevalent in various disciplines of study, including literary or fictional works. This study sheds light on postsecularism’s strengths of blending various theories such as postcolonialism and deconstruction, along with concepts from different thinkers, establishing its significance for exploring the injustice, domination and faultlines in society and particularly in literature and correcting them, which presents postsecularism as a significant theoretical lens.